The Development of Electronic Student Worksheet to Improving Higher Order Thinking Skills in Temperature and Heat Material - Elly Fathur Prayogi; Sri Wahyuni; Zainur Rasyid Ridlo (Postgraduate, University of Mataram, 2023)
This research aims to determine the validity, practicality and effectiveness of e-worksheet using the liveworksheet website. This research used method R&D which referred ADDIE model which consisted n five stages, Analysis, Design, Development, Implementation, Evaluation. Data collection techniques are validation sheets, student response questionnaires, interviews, observations, tests and documentation. The results showed that the developed media had met the following criteria: very valid (aspects of graphics, content, language) based on feasibility tests by expert groups who obtained an average percentage of 91%, Practical, based on the implementation sheet provided by three observers during the learning process using Electronic Student Worksheet products which get an average percentage of 95%, Effective, based on the results of pretest and postes used to determine HOTS thinking skills and use student response questionnaires after using the product. The result of the N-gain value obtained was 0.71 with a high category and a response questionnaire obtained of 90%. So that the development of an Electronic Student Worksheet is feasible to be used in the learning process because it has met the criteria of validity, feasibility and ease of use